no2.3061DETERMINASI KEUANGAN NEGARA GUNA MEWUJUDKAN KEADILAN SOSIAL (SOCIAL EQUITY) BAGI SELURUHRAKYAT INDONESIA - Simatupang, Dian Puji Nugraha (Jurnal Hukum & Pembangunan, 2021)
State finances in Indonesia is not totally determined by the social equity factor because they tend to be determined by the leadership of the government, so the meaning of state finances in order to realize the goals of the state is very dependent on the model and typical of the President as the holder of the highest state financial management in Indonesia.Such conditions cause state finances to be planned,budgeted, and accounted for with models and mechanisms in accordance with the Presidents management concept, and not on the concept of realizing the goals of the state to achieve social justice. This paper describes the strategic aspects of the paradigmatic state finance policy and state financial policy during the leadership of the Indonesian government, as well as the need toreform the state finance law in Indonesia that supports the realization of thepurposes of the state.